Application of β-Resorcylic Acid as Potential Antimicrobial Feed Additive to Reduce Campylobacter Colonization in Broiler Chickens - Wagle, Basanta R.; Upadhyay, Abhinav; Arsi, Komala; Shrestha, Sandip; Venkitanarayanan, Kumar; Donoghue, Annie M.; Donoghue, Dan J. (Frontiers in Microbiology, 2017)
Campylobacter is one of the major foodborne pathogens that result in severe gastroenteritis in humans, primarily through consumption of contaminated poultry products. Chickens are the reservoir host of Campylobacter, where the pathogen colonizes the ceca, thereby leading to contamination of carcass during slaughter. A reduction in cecal colonization by Campylobacter would directly translate into reduced product contamination and risk of human infections. With increasing consumer demand for antibiotic free chickens, significant research is being conducted to discover natural, safe and economical antimicrobials that can effectively control Campylobacter colonization in birds. This study investigated the efficacy of in-feed supplementation of a phytophenolic compound, β-resorcylic acid (BR) for reducing Campylobacter colonization in broiler chickens. In two separate, replicate trials, day-old-chicks (Cobb500; n=10 birds/treatment) were fed with BR (0, 0.25, 0.5 or 1 %) in feed for a period of 14 days (n=40/trial). Birds were challenged with a 4-strain mixture of C. jejuni (~ 106 CFU/ml; 250 µl/bird) on day 7 and cecal samples were collected on day 14 for enumerating surviving Campylobacter in cecal contents. In addition, the effect of BR on the critical colonization factors of Campylobacter (motility, epithelial cell attachment) was studied using phenotypic assay, cell culture and real-time quantitative PCR. Supplementation of BR in poultry feed for 14 days at 0.5 and 1% reduced Campylobacter populations in cecal contents by ~ 2.5 and 1.7 Log CFU/g, respectively (P<0.05). No significant differences in feed intake and body weight gain were observed between control and treatment birds fed the compound (P>0.05). Follow up mechanistic analysis revealed that sub-inhibitory concentration (SIC) of BR significantly reduced Campylobacter motility, attachment to and invasion of Caco-2 cells. In addition, the expression of C. jejuni genes coding for motility (motA, motB, fliA) and attachment (jlpA, ciaB) was down-regulated as compared to controls (P<0.05). These results suggest that BR could potentially be used as a feed additive to reduce Campylobacter colonization in broilers.